2006
DOI: 10.1007/s10551-006-9166-6
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Perceptions Regarding Ethical Marketing Practices: Affecting Change Through Instructional Techniques

Abstract: Many believe that colleges of business have a role to play in improving the level of marketing ethics practiced in the business world, while others believe that by the time students reach the level of university education, their ethical beliefs are so ingrained as to be virtually unalterable. The purpose of this study is to add to the literature regarding university students’ ethical value judgments. It utilizes scenario studies to assess base line ethical values of junior level undergraduate business administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…of responses Wynd and Mager (1989) No impact Ethical attitudes 550 business society university students in the United States Two separate groups (345) -pre + 205)-post Clark's questionnaire Personal ethics and social responsibility scores ''Stimulated'' pre/post using different student from different class of responses Weber and Green (1991) The list is revised and expanded from Glenn, Jr. (1992), who built on previous work by Weber (1990). This is not an exhaustive list and omits studies whose focus was not directly on impact of business ethics education (e.g., Bodkin and Stevenson, 2007;Cohen and Cornwell, 1989;Harris and Guffey, 1991;Lowry, 2003;MacFarlane, 2001;Ruegger and King, 1992;Surlin, 1987;Wittmer, 1992). Table I only includes studies assessing the impact of teaching an ethics or business and society class upon students, aiming to show a more targeted and updated list on business ethics education studies over the last three decades.…”
Section: Previous Studies On Ethics Educationmentioning
confidence: 99%
“…of responses Wynd and Mager (1989) No impact Ethical attitudes 550 business society university students in the United States Two separate groups (345) -pre + 205)-post Clark's questionnaire Personal ethics and social responsibility scores ''Stimulated'' pre/post using different student from different class of responses Weber and Green (1991) The list is revised and expanded from Glenn, Jr. (1992), who built on previous work by Weber (1990). This is not an exhaustive list and omits studies whose focus was not directly on impact of business ethics education (e.g., Bodkin and Stevenson, 2007;Cohen and Cornwell, 1989;Harris and Guffey, 1991;Lowry, 2003;MacFarlane, 2001;Ruegger and King, 1992;Surlin, 1987;Wittmer, 1992). Table I only includes studies assessing the impact of teaching an ethics or business and society class upon students, aiming to show a more targeted and updated list on business ethics education studies over the last three decades.…”
Section: Previous Studies On Ethics Educationmentioning
confidence: 99%
“…9 Litz (2003) gives evidence that participation-intensive classes are particularly appropriate when teaching ethics to business students. Bodkin and Stevenson (2007) conclude their study with the observations that, Time for reflection has been shown to have a bearing on ethical perceptions. Suggestions for marketing instructors would include increasing the amount of active time discussing marketing ethics and passive time thinking about ethical dilemmas.…”
Section: The Role Of Universities In Cultivating Ethical Leadership Amentioning
confidence: 81%
“…Authors also disagree about the extent to which teaching ethics influences how people will behave. While most might agree with Bodkin and Stevenson (2007) that "it is difficult to affect long-run change in those predisposed to unethical behaviour," nobody knows how many people have such predispositions or how and why such predispositions contribute to behaviour. 8 Much of the variability in these studies involves evaluating different methodological approaches to ethics instruction.…”
Section: The Role Of Universities In Cultivating Ethical Leadership Amentioning
confidence: 99%
See 1 more Smart Citation
“…In this design, the dependent variable is measured in training and control groups at the same times, before and after the training occurs. Several prior studies on business ethics training have not included a control group (e.g., Abolmohammadi and Reeves, 2000;Bodkin and Stevenson, 2007;Carlson and Burke, 1998;Dellaportas, 2006;Desplaces et al, 2007;Fraedrich et al, 2005;Weber and Glyptis, 2000;Wynd and Mager, 1989). Moreover, in some of the studies in which a control group was included, preand post-training measures were not obtained at the same times in both groups (e.g., Glenn, 1992;Zinkhan et al, 1989).…”
Section: Methodological Considerationsmentioning
confidence: 99%